PDn-3 DPA Pathway Regulates Human Monocyte Differentiation and Macrophage Function. Issue 6 (21st June 2018) - Pistorius, Kimberly; Souza, Patricia R.; De Matteis, Roberta; Austin-Williams, Shani; Primdahl, Karoline G.; Vik, Anders; Mazzacuva, Francesca; Colas, Romain A.; Marques, Raquel M.; Hansen, Trond V.; Dalli, Jesmond
Summary: Macrophages are central in orchestrating the clearance of apoptotic cells and cellular debris during inflammation, with the mechanism(s) regulating this process remaining of interest. Herein, we found that the n-3 docosapentaenoic acid-derived protectin (PDn-3 DPA ) biosynthetic pathway regulated the differentiation of human monocytes, altering macrophage phenotype, efferocytosis, and bacterial phagocytosis. Using lipid mediator profiling, human primary cells and recombinant enzymes we found that human 15-lipoxygenases initiate the PDn-3 DPA pathway catalyzing the formation of an allylic epoxide. The complete stereochemistry of this epoxide was determined using stereocontrolled total organic synthesis as 16 S, 17 S -epoxy-7 Z, 10 Z, 12 E, 14 E, 19 Z -docosapentaenoic acid (16 S, 17 S -ePDn-3 DPA ). This intermediate was enzymatically converted by epoxide hydrolases to PD1n-3 DPA and PD2n-3 DPA, with epoxide hydrolase 2 converting 16 S, 17 S -ePDn-3 DPA to PD2n-3 DPA in human monocytes. Taken together these results establish the PDn-3 DPA biosynthetic pathway in human monocytes and macrophages and its role in regulating macrophage resolution responses. Graphical Abstract: Highlights: PDn-3 DPA regulates human monocyte-derived macrophage differentiation and function Evidence for the formation and complete stereochemistry of 16 S, 17 S -ePDn-3 DPA EPHX2 converts 16 S, 17 S -ePDn-3 DPA to PD2n-3 DPA in human monocytes Abstract : Pistorius et al., found that a recently uncovered family of bioactive mediators termed PDn-3 DPA controls human macrophage phenotype and function during their differentiation from monocytes. The authors also established the biosynthetic pathway for this family of mediators thereby providing leads into mechanisms that control macrophage responses.